Additional field player tactics` effects to match performance during the numerical asymmetric situations in female handball - Gümüs, H.; Sahin, T.; Gencoglu, C. (Turkish Journal of Sport and Exercise, 2020)
The aim of this study was to analyze to effects of additional field player rule as a tactical intervention in elite female handball. The thirty-nine highly competitive handball matches were undergone notational analysis from 2020 IHF Women`s World Championship. Goal, 7-m and 2-min penalty, missed shots, technical errors, received goal empty net, missed shots empty net, fast break goals and substitution failures analyzed during the goalkeeper benched durations for tolerate the numerical inferiority or creating numerical asymmetry to attack with an extra player for each 10-min periods. There was a significant difference between 5&6 and 7&6 situations however no statistically significant differences all parameters in both situations in comparison winner and loser teams. Moreover, we did not observe significantly changes all parameters when compared the match periods in 5&6 and 7&6 situations. These findings suggested that current tactical variation more frequently used by teams to tolerate the numerical inferiority in the attack whereas the consequences of application has a low risk to receive goal the empty net. Current findings of this study teams which used the additional field player strategy has no extra attacking efficiency however this tactical application does not result in any negative effects within risk of empty goalie